Knockdown Fascin impairs bone marrow mesenchymal stem cells migration capacity of Wuzhishan Miniature pig - YANG, LING; XIA, YING; TAO, XIAO-LI; HE, WEI; WU, TIAN-WEN; HUANG, LEI; RUAN, JIN-XUE; YANG, SHU-LIN; MU, YU-LIAN; LI, KUI; FENG, SHU-TANG (The Indian Journal of Animal Sciences, 2014)
The bone marrow mesenchymal stem cells (BM-MSCs) from Wuzhishan pig (WZSP) with knockdown expression of Fascin were used to make out the role Fascin gene in migratory potential of BM-MSCs. The role of Fascin gene is well established in cellular migration, but it is unclear for its activity in porcine BM-MSCs. At present study, BM-MSCs were isolated from femur and tibia of the WZSP with about 42 day-old, and had been evaluated by previous study. At first, 4 vectors encoding different short hairpin RNA (shRNA) for Fascin were designed to knock down Fascin, and qRT-PCR was employed to detect the expression of Fascin mRNA by BM-MSCs after transfection, and the vector with best interference effect was selected to be used in the following experiments. And then, the effect of knock down Fascin was further determined through Western blot using Fascin antibody. Finally, the migration capacity of the BM-MSCs was evaluated through scratch assay and transwell migration assay. The results showed that the specific shRNA for knocking down Fascin efficiently was found for the BM-MSCs from WZSP, and Fascin was involved in regulating the migration capacity of the BM-MSCs in vitro, which may be useful for the BM-MSCs from WZSP to be utilized in regenerative therapy for human.